A highly selective fluorescent sensor for dual detection of Zn2+ and F− based on a new diarylethene. Issue 25 (22nd June 2016) - Tian, Zhaoyan; Cui, Shiqiang; Pu, Shouzhi
Graphical abstract: A new asymmetrical diarylethene with a coumarin moiety was synthesized and its multi-functional fluorescent switching behaviors were investigated. The diarylethene was highly selective towards Zn 2+ and F − with different fluorescent color and binding modes. Highlights: A novel diarylethene with coumarin unit was synthesized. It could be served as a multi-functional fluorescent switching induced by light, Zn 2+ /EDTA, and F − . The diarylethene derivative could be used as a selective fluorescence sensor for the recognition of Zn 2+ and F −, respectively. Abstract: A new diarylethene derivative with a coumarin unit was synthesized. Its multi-functional fluorescent switching behaviors were investigated by the stimulation of UV/vis light, Zn 2+ /EDTA, and F − . The diarylethene was highly selective toward Zn 2+ and F − with different fluorescence colors and binding modes. Upon addition of Zn 2+, its emission peak was blue-shifted by 32 nm and emission intensity was enhanced by 57 fold, due to the formation of a 1:1 metal/ligand complex, accompanied by a fluorescence color change from dull red to green. Moreover, the diarylethene was also selectivity to F − with the fluorescence color change from dull red to yellow. The dramatic fluorescence color change made the naked eye detection of Zn 2+ and F − possible.